Integrated techno-economic analysis under uncertainty of glycerol steam reforming for H2 production at distributed H2 refueling stations. (15th January 2019) - Lee, Boreum; Heo, Juheon; Kim, Sehwa; Kim, Chang-Hyun; Ryi, Shin-Kun; Lim, Hankwon
Highlights: Performing integrated analysis of glycerol steam reforming for H2 production. Obtaining ranges of unit H2 production cost and B/C ratio from uncertainty analysis. Economic viability for glycerol steam reforming in distributed H2 refueling station. Abstract: In this paper, we report an integrated techno-economic analysis of glycerol steam reforming (GSR) targeting distributed H2 refueling stations for a H2 production capacity of 700 m 3 h −1 . A process simulation based on mass and energy balances was performed to identify the product yield at effect of temperature and water/glycerol ratio. The results show that temperature of 900 K and a water/glycerol ratio of 9 are optimal to techno-economically operate a GSR process. An economic analysis using itemized cost estimation, sensitivity analysis (SA), and profitability analysis (PA) was carried out to investigate the economic feasibility of GSR for distributed H2 refueling stations. The unit H2 production cost was 4.46 kgH2 −1 at the optimum conditions identified in the process simulation, and the most influential economic key factor was the reactant from the SA. Meaningful economic indicators such as net present value, discounted payback period, present value ratio, and rate of return on investment were obtained from the PA through a discounted cash flow diagram. Moreover, a cumulative probability analysis based on an uncertainty analysis using a Monte-Carlo simulation method was applied to unit H2 production cost and B/C ratio calculations to quantify the risk of a proposed GSR process as premature technology providing crucial guidelines to decision-makers.